Exports, Imports, and Economic Growth in North Korea - Kim, Byoungki; Kyophilavong, Phouphet; Ryu, Geun Woo (International Journal of Multidisciplinary in Management and Tourism, 2020)
North Korea is trying to transit its economic system towards market oriented economy. Many transition economies have experienced rapid growth through inflow of foreign capital and expansion of exports. The objective of this paper is to investigate relationship between trade and economic growth in North Korea. We employed Johansen cointegration test and Granger causality test for this study using annual data over the period from 1991 to 2015 that is based on data available. Empirical results found that there is a long-run relationship between exports and growth, and imports and growth. And there is uni-directional causality running from exports to growth, and bi-directional causality between imports and growth in North Korea. These results reveal that export expanding policy will stimulate exports and economic growth. Imports also stimulates economic growth in North Korea. We can conclude that introduction of open-door policy is essential for sustainable economic growth in North Korea. North Korea has a high potential for rapid growth because of rich natural resources and geographical advantage located among Asia’s biggest economy China, South Korea and Japan. North Korea could fully enjoy the latecomer’s advantage in economic development lessons that experienced by many transition economies. The politic reform and economic reform may attract foreign capital and it strongly stimulates North Korea’s trade. Therefore, North Korea should promote the export in order to promote economic growth by introduction of open-door policy and economic reform such as guarantee of foreign direct investment, trade liberalization, trade facilitation, and eliminate the non-tariff barriers.